2010
DOI: 10.1089/tmj.2010.0079
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy and Image Quality Using a USB Digital Eyepiece Camera for Telecytology—Georgian Experience

Abstract: digital images for cytology diagnostic are of adequate quality, with diagnostic concordance rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The Republic of Georgia study (n = 420) evaluated the effectiveness of digital images for telecytology diagnosis. 150 Four cytologists provided diagnoses using digital images. ''There was 94% concordance in average between routine versus digital images diagnostic.…”
Section: Empirical Foundations Of Telepathologymentioning
confidence: 99%
“…The Republic of Georgia study (n = 420) evaluated the effectiveness of digital images for telecytology diagnosis. 150 Four cytologists provided diagnoses using digital images. ''There was 94% concordance in average between routine versus digital images diagnostic.…”
Section: Empirical Foundations Of Telepathologymentioning
confidence: 99%
“… 15 27 29 43 46 48 49 Moreover, 11 studies investigated the effectiveness of telecolposcopy where an experienced clinician had made decisions and diagnosis remotely. 14 16 17 21 25 26 42 44 45 47 TM has also been used for collaboration and training between clinicians and medical students; for example, e-consultations between primary and secondary care clinicians discussing the care of patients 23 and in teleconferences providing expert and multidisciplinary input in oncological cases. 28 33 41 Furthermore, the role of TM in medical education has been assessed in three studies where trainees were provided feedback from an experienced surgeon remotely, during real-time surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Kldiashvili et al 23 evaluated ‘telecytology’ whereby 420 cytological images were assessed by on-site and off-site cytologists. 23 The study found a 94% concordance between routine versus digital images and 97% of digital images were rated as ‘good’ or ‘excellent’.…”
Section: Resultsmentioning
confidence: 99%
“…Ayatollahi et al [2] found an interobserver reproducibility of 0.71 between two institutions in Iran and United States of America for pleural cytology. In a large study of 420 cases, Kldiashvili and Schrader [3] showed a concordance of 94% for gynecologic cytology between routine microscopy and telecytology. Caron et al [4] found 100% interobserver concordance between submitting institutions and the referral centre for 10 cases of fine needle aspiration and 10 cases of gynecologic pathology by using whole slide digital imaging for telecytology consultation.…”
Section: Introductionmentioning
confidence: 99%